Callus Induction, Regeneration of Rice Variety BRRI Dhan29 and Determination of Lethal Dose Of Ethyl Methanesulfonate - Khan, NA; Uddin, MI; Ghosh , JK; Rashid, MH (Bangladesh Journal of Nuclear Agriculture, 2023)
Rice is an essential meal for a large section of the world's population including Bangladesh. BRRI Dhan29 is known as an excellent rice variety in Bangladesh but it is now susceptible to several diseases and pests, which might reduce rice yields. Therefore, it becomes necessary to explore and optimize different approach with the aim of enhancing yield, diseases resistance and overall genetic variability of this important rice variety. Ethyl methanesulphonate (EMS) produces a large number of non-lethal point mutations by alkylates guanine bases and leads to mispairing-alkylated guanine pairs with thiamine instead of cytosine. The LD50 of EMS is frequently used as a general indicator of a substance's acute toxicity and a lower LD50 is indicative of increased toxicity. This study aimed to develop a comprehensive protocol for callus induction, regeneration for the BRRI dhan29 rice and to determine the LD50% of EMS on callus survival for further genetic improvement. Mature embryos were used to induce callus by utilizing different concentrations (0.00, 0.5, 1.00, 1.50, 2.00, 2.50, 3.00 and 3.50 mg/L) of 2,4-Dichlorophenoxyactic acid (2, 4-D), while callus regeneration was studied using varying combine concentrations of 1-naphthaleneacetic acid (NAA: 0, 5, 10 and 15 μg/L) and kinetin (0.00, 1.00, 2.00 and 3.00 ml/L). The optimal concentrations for callus induction was 2.0 mg/L 2, 4-D and a combination of 10 μg/L NAA and 2.0 mg/L kinetin were identified for efficient callus regeneration. The LD50 of EMS on BRRI dhan29 calli was 0.31%, indicating its potential mutagen for creating genetic variations. Regenerated plants were successfully acclimatized at field conditions. These findings might provide valuable insights for tissue culture-based studies and genetic improvement efforts for the BRRI dhan29. Bangladesh J. Nuclear Agric, 37(1): 1-10, 2023